Variação linguística na concordância nominal de número em comentários na rede social Facebook - Leite, Jessica Bianchi (2019)
According to the theoretical assumptions of Variationist Sociolinguistics, especially from Labov’s theory (2008[1972]), this research proposes an analysis of the phenomenon of nominal number agreement in writing on virtual environment, more precisely on comments of institutional pages and public figures pages on social network Facebook. Starting from the description of variation in nominal agreement of number in speaking, widely described by Scherre (1988), and given the trend of approximation of the writing in virtual environment with orality (RECUERO, 2014), this work has as a hypothesis that the same performed descriptions for the phenomenon of nominal number agreement as those found in writing on virtual environment as well. The object is the collection of comments found on the social network, found in two pages of institutions and other two pages of public figures. What is proposed is to find out if the varieties that are shown in writing on virtual environment are shown in the same way as on orality, that is, if the speaker uses the same varieties that they do in speaking, on number nominal agreement.The question is: the samples of non-agreement of number in the virtual environment could be systematized as those in speaking? As specific objectives, we have: observe which variations are shown as similar to the varieties in orality and which ones show different aspects; classify the comments on which ones do not perform the nominal agreement in all the flexible nominal elements, found according to the varieties determined by the theory and research read (LABOV, 2008[1972]); (SCHERRE, 1988); (FERNANDES, 1996); (MENON et al, 2016); (FONSECA et al, 2018). The linguistics varieties raised for the basis of analysis were as follows: explicit plural mark found and syntagmatic configuration (SCHERRE, 1988); phonogram and phonological word (MENON et al, 2016); previous marks (FONSECA et al, 2018). As assumptions, we have a situation in which the speaker does not recognize the social network as a requester of a formal variety; stigmatized standards might not be found, due to the fact that not everybody has access to internet connection. The non-agreement of nominal number that occurs in the virtual environment can or not represent what occurs in orality, and, on cases which they do not represent, could be lapsus linguae. The primary conclusion is that writing in the virtual environment can be in modification while the speaker transcribes to other communicative spaces of this environment the varieties that they do in orality. However, the research about linguistic variation in writing were not enough to assume a change, neither this research, which is needed of enhancement in the mechanism of data collection, making it possible to access extralinguistic data.